Synthesis and Antiproliferative Activities of Novel Substituted 5‐Anilino‐α‐Glucofuranose Derivatives. Issue 4 (20th April 2020) - Zhang, Yaling; Wang, Lili; Sun, Baoli; Li, Xiabing; Hou, Qiaoli; Wang, Wei; Li, Baolin
Abstract: In order to find novel antitumor candidate agents with high efficiency and low toxicity, 14 novel substituted 5‐anilino‐ α ‐glucofuranose derivatives have been designed, synthesized and evaluated for antiproliferative activities in vitro. Their structures were characterized by NMR ( 1 H and 13 C) and HR‐MS, and configuration ( R / S ) at C(5) was identified by two‐dimensional 1 H, 1 H‐NOESY‐NMR spectrum. Their antiproliferative activities against human tumor cells were investigated by MTT assay. The results demonstrated that most of the synthesized compounds had antiproliferative effects comparable to the reference drugs gefitinib and lapatinib. In particular, (5 R )‐5‐ O ‐(3‐chloro‐4‐{[5‐(4‐fluorophenyl)thiophen‐2‐yl]methyl}anilino)‐5‐deoxy‐1, 2‐ O ‐(1‐methylethylidene)‐ α ‐glucofuranose (9da ) showed the most potent antiproliferative effects against SW480, A431 and A549 cells, with IC 50 values of 8.57, 5.15 and 15.24 μm, respectively. This work suggested 5‐anilino‐ α ‐glucofuranose as an antitumor core structure that may open a new way to develop more potent anti‐cancer agents. Abstract :